Correlation between Cell Proliferation with Cervical Lymphoid Node Status in Nasopharyngeal Carcinoma Patients - Nugroho, Puguh Setyo; Yusuf, Muhtarum; Hidayati, Titiek Ahadiyah (Folia Medica Indonesiana, 2021)
Several studies showed that the index of nasopharyngeal carcinoma (NPC) cell growth could be used to assess the carcinogenesis interaction factor, development and prognosis of NPC. Cell proliferation index could always be assessed with Ki-67 protein expression test. This research was conducted to study the correlation between cell proliferation index with cervical lymphoid node status in NPC in clinical manifestation to asses the progressivity and prognosis on NPC patients. This study used cross sectional design. Biopsy tissue specimen were acquired from 35 NPC patients clinically divided into four criteria of cervical lymphoid node status (N0, N1, N2 and N3). Expression of Ki-67 protein was acquired by immunohistochemistry test using monoclonal rabbit antibody anti-human Ki-67 clone 901-325-091911 (Biocare Medical, LCC. 4040 Pike Line, CA 94520 USA). The measurement of Ki-67 protein was conducted by pathology consultant. Spearman statistic test was performed to asses the correlation between Ki-67 protein expression and cervical lymphoid node status. The statistical significance was defined as p<0.05. Positive expression of Ki-67 protein was found in 33 patients; 4 patients with N0 (11.43%), 5 patients with N1 (14.29%), 9 patients with N2 (25.71%), and 15 patients with N3. Negative expression of Ki-67 protein was found in 2 patients with N0 (5.71%). The Spearman test resulted at p=0.0001 with correlation coefficient of 0.758. The correlation between Ki-67 protein expression with cervical lymphoid node resulted in a significant correlation (p<0.05). In conclusion, cell proliferation index has correlation with cervical lymphoid node status in NPC patients.